2009
DOI: 10.1074/jbc.m809802200
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Motif within the NH2-terminal Coiled-coil Domain of Angiopoietin-like Protein 4 Confers Its Inhibitory Effects on Lipoprotein Lipase by Disrupting the Enzyme Dimerization

Abstract: Lipoprotein lipase (LPL) is a principal enzyme responsible for the clearance of chylomicrons and very low density lipoproteins from the bloodstream. Two members of the Angptl (angiopoietin-like protein) family, namely Angptl3 and Angptl4, have been shown to inhibit LPL activity in vitro and in vivo. Here, we further investigated the structural basis underlying the LPL inhibition by Angptl3 and Angptl4. By multiple sequence alignment analysis, we have identified a highly conserved 12-amino acid consensus motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 44 publications
(63 reference statements)
3
81
0
Order By: Relevance
“…It is composed of 406 amino acids and contains an amino-terminal coiled-coil domain and a carboxyl-terminal fibrinogen-like domain (3). The most studied functions of Angptl4 are its role in the regulation of angiogenesis, glucose metabolism and lipid metabolism (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of 406 amino acids and contains an amino-terminal coiled-coil domain and a carboxyl-terminal fibrinogen-like domain (3). The most studied functions of Angptl4 are its role in the regulation of angiogenesis, glucose metabolism and lipid metabolism (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by population-based studies that indicate that individuals carrying the E40K variant of Angptl4 have low plasma triglyceride levels (26). Furthermore, a synthetic peptide spanning residues 44 -55 of human Angptl4 was able to inhibit LPL, but the affinity of this peptide for LPL was much lower than that of full-length ccd-Angptl4 (25).…”
mentioning
confidence: 81%
“…This was supported by fluorescence measurements, demonstrating that fatty acids hinder the accessibility of the quencher acrylamide to the single Trp residue of ccd-Angptl4. This residue (Trp-38) is located close to the putative binding site for LPL (24,25). It has been previously shown that ccd-Angptl4 induces inactivation of LPL by causing dissociation of dimeric LPL into inactive monomers (10).…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies employing transgenic mice overexpressing angptl4 specifically in white adipose tissue have shown that this protein significantly decreased postheparin plasma LPL activity [17]. Numerous studies have provided firm evidence that angptl4 irreversibly inhibits LPL activity which is at least partly accounted for by promoting the conversions of active LPL dimers into inactive monomers [18]. In rodents, angptl4 is most highly expressed in adipose tissue followed by the liver, intestine, heart, kidney and ovary [19].…”
Section: Introductionmentioning
confidence: 99%